Portable data acquisition and fluidic system for electrochemical Sensors - Azmi, Nur Hanisah; Nordin, Anis Nurashikin; Suhaimi, Muhammad Irsyad; Meng, Lim Lai; Ab Rahim, Rosminazuin; Bashri, Mohd Saiful Riza; Samsudin, Zambri (IEEE, 2023)
The recent outbreak of infectious diseases has highlighted the necessity of point-of-care detection compared to central lab analysis for more effective epidemic control. Recent developments in the field of biosensors have allowed sensitive, accurate disease diagnosis using low-cost devices. In this work, we describe the development of a portable data acquisition and fluidic system for miniature electrochemical biosensors. The data acquisition system was designed as a single printed circuit board and can perform cyclic voltammetry. The fluidic chamber was designed to work with three miniature sensors which are placed on a single platform. Leakage tests were performed to ensure that each chamber allows sensor isolation and avoids any cross- contamination. Measurements using the fabricated potentiostat board were taken and compared with a commercial potentiostat. It was found that the designed potentiostat was able to measure the same resolution and peak separation in cyclic voltammetry measurements.